The Effect Transformational Leadership Style on Job Performance: The Mediating Role of Trust at PT Varia Usaha Beton - Dewi Fatimah; Dwiarko Nugrohoseno (Lavish Opulent Education, 2025)
This research aims to test and analyze he influence of transformational leadership style on job performance through trust at PT Varia Usaha Beton. This research uses a quantitative methods. The sampling technique used is non-probability sampling with a saturated sample, in which the entire population is used as the sample with 40 respondents. Data were analyzed using partial least squares (PLS) with the SmartPLS 3.0 software. The results show that transformational leadership style has a positive and significant effect on job performance. Transformational leadership style also has a positive and significant effect on trust in leader. Furthermore, trust in leader has a positive and significant effect on job performance. The path analysis further reveals that trust in leader functions as a mediating variable in the relationship between transformational leadership style and job performance.